Role of Government Interest Sarereiket Hold in Village in District Madobag Mentawai Islands - Sayid Anshar (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2019)
The problem in this study is How the Sarereiket Tribe Role in organizing Government in the Village of Madobag Mentawai Islands District. The purpose of this study was to determine the Role of the Sarereiket Tribe in organizing Government in Madobag Village, Mentawai Islands Regency. This study uses qualitative and descriptive methods. In this study, the population is Madobag village apparatus, village representative body (BPD), hamlets, tribal organizations, community shops and Madobag village community environment. The sample in this study is Madobag village apparatus six people, one village representative body (BPD), three hamlet heads, two community shops and two people in the Madobag village environment. with purposive sampling technique. Based on the results of this study it is suggested that to realize good leadership at the village level, the village head must play a greater role in every village administration activity that concerns the public interest and is clearer in making decisions and being fair and being consistent in carrying out decisions especially in Sarereiket tribal governance in the village of Madobag.